What every teacher should know about reading comprehension instruction - Pearson, P. David; Harvey, Stephanie; Goudvi, Anne (Portsmouth, NH : Heinemann, 2005)
An interview session with renowned reading resercher and comprehension theorist P. David Pearson to get the inside scoop on the research behind high-quality comprehension instruction
Editor, Lois Bridge ; DVD production, Kevin Carlson
Keywords: Reading comprehension